Exploring GovTech Practices in Indonesia: Potential, Barriers and Lesson Learned - Likuwatan Werang, Nicolaus Petrus; Werang, Maria Lusiana Florentin; Rizki, Mia (Faculty of Social and Political Science Universitas Brawijaya, 2025)
The adoption of GovTech in Indonesia is still relatively minimal, with several reflections (e.i., potential, obstacles and lessons learned) in concretisation not yet fully actualised proportionally and consistently through the government as the party responsible. Pertinent to this, this study focuses on the actualisation of GovTech in Indonesia and other countries as empirical evidence in the analysis to find applicable solutions, with a focus on potential barriers and lessons that can be educated from the transformation process, especially the digitalisation of the public sector through GovTech practices. The findings display limited infrastructure, a digital skills gap among government employees, and resistance to technological change in comprehensive GovTech practices. Thereupon, urgency emphasised from this that in building GovTech, it is necessary to pay attention to the element of public trust, involve citizens in the change process, and encourage collaboration between the government/private sector, which is highly emphasised in GovTech practices. Notwithstanding GovTech can elevate transparency, service quality, and citizen involvement, its adoption in Indonesia still faces significant barriers, including uneven concretisation between regions and a lack of resources and training. Finally, we underline the solution requires a more intensive approach, including expanding digital access, training for government employees, and building public trust in GovTech practices.